Effects of CaO, MgO, Al2O3 and SiO2 on the carbothermic reduction of synthetic FeCr2O4 - Wang Y.; Wang L.; Chou K.C. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In order to optimize the current reduction process of chromite, a good knowledge of reduction mechanism involved is required. The basic component in chromite ore is FeCr2O4 with gangue component like MgO and Al2O3. In lack of clear and consistent explanation about the effect of addition on the reduction of FeCr2O4, investigation of synthetic FeCr2O4 with different kind and amount of additions was carried out at 1673K under isothermal mode. Kinetic mechanism was also studied by linear fitting of different kinetic equations. Combined with rate-controlling step, it could be concluded as follows. CaO could enhance the reduction because Ca2+ would replace Fe2+, thus facilitated the ion diffusion in solid phase. Al2O3 had a positive influence as well, since Al3+ could form a solid solution phase with Cr3+ and made Cr3+ reduced more easily. MgO would hinder the reduction due to formation of a more stable phase MgCr2O4. SiO2 would also hamper the Cr metallization because there was a liquid phase formed when Cr3+ was reduced to divalent, which would impede the nucleation of reduction product.